CUSTOMER PREFERENCE TOWARDS SERVICES RENDERED BY SHOPPING MALLS IN CHENNAI CITY - Vinotha, Dr. M. Gurupandi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The observe of the study shopping is an important part of life for an all individual. The change in living style of the people, they prefer to buy from a place where they can buy everything under one roof. The economic development and the change in consumer culture, shopping malls in India have extraordinary growth and replaced the traditional departmental store and retail outlet. The main objective of the study customers and level of preference towards services rendered by shopping malls in Chennai city. The study includes both primary and secondary data. Primary data collected from customer through the questionnaire method, the sample size is 360. A convenient sampling method was used for the study. The concluded of the study shopping malls attract buyers and sellers, and attract customers, providing sufficient time to make varieties as well as a entertaining means of shopping. However, competition between malls, blocking of markets and traditional shopping centres has led mall inventors and management to consider alternative methods to size enjoyment in customers. Shopping malls, collection of stores, sales promotions and comparative economic gains in the malls attract higher customer movement to the malls. Shopping ways and the rise of shopping malls have been major trends in retailing in emerging markets.